2000
DOI: 10.2514/2.6506
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Dual Reciprocity Boundary Element/Finite Volume Method for Transient Conjugate Heat Transfer

Abstract: A coupled nite volume/dual reciprocity boundary element method is developed to solve the transient conjugate heat transfer problem of convective heat transfer over and conduction heat transfer within a solid body. In this approach, the ow eld and forced convection heat transfer external to the body is resolved by numerically solving the time-dependent Navier-Stokes equations using a nite volume method, whereas the temperature eld within the body is resolved by numerically solving the heat conduction equation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…With the development in computational tools, other techniques such as inverse analysis using control volume heat balance [11], inverse finite‐element analysis [3, 12], and genetic algorithms [13] have been reported in the literature for prediction of surface heat flux. Very recently, a numerical technique using conjugate heat transfer (CHT) analysis has been established and is considered as one of the options to forecast the surface heat flux [14.]…”
Section: Introductionmentioning
confidence: 99%
“…With the development in computational tools, other techniques such as inverse analysis using control volume heat balance [11], inverse finite‐element analysis [3, 12], and genetic algorithms [13] have been reported in the literature for prediction of surface heat flux. Very recently, a numerical technique using conjugate heat transfer (CHT) analysis has been established and is considered as one of the options to forecast the surface heat flux [14.]…”
Section: Introductionmentioning
confidence: 99%
“…The BEM is used to solve solid heat conduction problem. He et al [13,14], M He et al [15], Kontinos [16], Rahaim and Kassab [17] and Rahaim et al [18] adopted this conjugate heat transfer analysis method to solve different coupled problems. Kassab et al [19] reported on the coupling of the BEM method with the Glenn-HT code.…”
Section: Introductionmentioning
confidence: 98%
“…Several solver couplings are also dedicated to very specific configurations, with specific geometries or solvers (studies in the fields of space [11], combustion [12,13]). Besides, more and more unsteady applications can be found in the literature [5,[12][13][14][15]21].…”
Section: Introductionmentioning
confidence: 99%